In Vitro and In Vivo Effect of the Imidazole Luliconazole against Lomentospora prolificans and Scedosporium spp. - Dan-Tiberiu Furnica; Silke Dittmer; Ulrike Scharmann; Jacques F. Meis; Joerg Steinmann; Peter-Michael Rath; Lisa Kirchhoff (Microbiology Spectrum, 2023)
ABSTRACT Infections with Scedosporium spp. and Lomentospora prolificans have become a serious threat in clinical settings. The high mortality rates associated with these infections can be correlated with their multidrug resistance. The development of alternative treatment strategies has become crucial. Here, we investigate the in vitro and in vivo activity of luliconazole (LLCZ) against Scedosporium apiospermum (including its teleomorph Pseudallescheria boydii) and Lomentospora prolificans. The LLCZ MICs were determined for a total of 37 isolates (31 L. prolificans isolates, 6 Scedosporium apiospermum/P. boydii strains) according to EUCAST. Furthermore, the LLCZ antifungal activity was tested in vitro, using an XTT [2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-5-carboxanilide salt] growth kinetics assay and biofilm assays (crystal violet and XTT assay). In addition, a Galleria mellonella infection model was used for in vivo treatment assays. The MIC90 of LLCZ was determined to be 0.25 mg/L for all tested pathogens. Growth was inhibited within 6 to 48 h of the start of incubation. LLCZ inhibited biofilm formation in both preadhesion stages and late-stage adhesion. In vivo, a single dose of LLCZ increased the survival rate of the larvae by 40% and 20% for L. prolificans and Scedosporium spp., respectively. This is the first study demonstrating LLCZ activity against Lomentospora prolificans in vitro and in vivo and the first study showing the antibiofilm effect of LLCZ in Scedosporium spp. IMPORTANCE Lomentospora prolificans and S. apiospermum/P. boydii are opportunistic, multidrug-resistant pathogens causing invasive infections in immunosuppressed patients and sometimes in healthy persons. Lomentospora prolificans is panresistant against the currently available antifungals, and both species are associated with high mortality rates. Thus, the discovery of novel antifungal drugs exhibiting an effect against these resistant fungi is crucial. Our study shows the effect of luliconazole (LLCZ) against L. prolificans and Scedosporium spp. in vitro, as well as in an in vivo infection model. These data reveal the previously unknown inhibitory effect of LLCZ against L. prolificans and its antibiofilm effect in Scedosporium spp. It represents an extension of the literature regarding azole-resistant fungi and could potentially lead to the development of future treatment strategies against these opportunistic fungal pathogens.